(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Intrigued by our recent experimental work (H. Yamaguchi and X. D. Niu, J. Fluids Eng., 133 (2011), 041302), the present study numerically investigate the flow-structure interactions (FSI) of three rigid circular particles aligned moving in an inclined channel flow at intermediate Reynolds numbers by using a momentum-exchanged immersed boundary-lattice Boltzmann method. A "frog-leap" phenomenon observed in the experiment is successfully captured by the present simulation and flow characteristics and underlying FSI mechanisms of it are explored by examining the effects of the channel inclined angles and Reynolds numbers. It is found that the asymmetric difference of the vorticity distributions on the particle surface is the main cause of the "frog-leap" when particle moves in the boundary layer near the lower channel boundary.